2012
DOI: 10.1097/qai.0b013e31826cba6c
|View full text |Cite
|
Sign up to set email alerts
|

Association of Regional Body Composition With Bone Mineral Density in HIV-Infected and HIV-Uninfected Women

Abstract: Objective To understand how regional body composition affects bone mineral density (BMD) in HIV-infected and uninfected women. Methods Dual energy X-ray absorptiometry was used to measure regional lean and fat mass and BMD at lumbar spine (LS), total hip (TH), and femoral neck (FN) in 318 HIV-infected and 122 HIV-uninfected Women's Interagency HIV Study participants at baseline and 2 and 5 years later. Total lean and fat mass were measured using bioimpedance analysis. Multivariate marginal linear regression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 51 publications
1
27
0
Order By: Relevance
“…In a cohort of HIV-infected and uninfected women, total fat was found to be independently associated with increased BMD. 19 The difficulty in defining Bskin color[ in a population such as this one, in which miscegenation is high, may have acted as a confounding factor. Finally, the lack of any association with known risk factors, such as smoking or alcohol consumption, may have been negatively affected by the variation in the use of these substances in a woman's lifetime.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In a cohort of HIV-infected and uninfected women, total fat was found to be independently associated with increased BMD. 19 The difficulty in defining Bskin color[ in a population such as this one, in which miscegenation is high, may have acted as a confounding factor. Finally, the lack of any association with known risk factors, such as smoking or alcohol consumption, may have been negatively affected by the variation in the use of these substances in a woman's lifetime.…”
Section: Discussionmentioning
confidence: 96%
“…The associations of total fat and regional body composition with BMD were also evaluated in these women; greater trunk fat was associated with increased BMD, suggesting different mechanisms by which regional body fat may affect BMD, including changes in lipid metabolism and body composition. 19,20 In middle-aged women, postmenopausal estrogen deprivation is another factor directly related to HIV infection that may aggravate this risk of bone mass loss. 21 Although the cause of low BMD in HIV-infected individuals is probably multifactorial, Pinto Neto et al 22 reported that, in a group of HIV-infected women, postmenopausal women had the highest risk for developing low BMD.…”
mentioning
confidence: 99%
“…The Boston Area Community Health/Bone (BACH/Bone) Survey performed DXA at baseline and 7-year follow-up in 692 HIV-uninfected men [15]. From the metabolic sub-study of the Women's Interagency HIV Study (WIHS), we utilized whole body DXA results at baseline and 5-year follow-up in 122 HIV-uninfected women [16]. We excluded data from HIV-uninfected participants in these studies outside the sex-specific age window of the HIV-infected study participants (age range of HIV-infected men and women at initial DXA was 20 to 64 years and 23 to 55 years, respectively) and assumed a linear rate of body composition change among HIV-uninfected individuals.…”
Section: Methodsmentioning
confidence: 99%
“…28 Second, body weight and body fat composition are known to influence bone metabolism in normal populations, 29 and these factors are of particular importance among patients with HIV-1 infection who may be underweight or develop fat redistribution syndrome. 30 In a further sub-analysis of CASTLE data, ATV/r-treated patients within the lowest BMI category (,22 kg/m 2 ) showed a significant increase in both visceral and subcutaneous adipose tissues compared with LPV/r patients and also a significant increase in trunk:limb fat ratio. 31 Thus, a greater "return to health" phenomenon in ATV/r-treated patients compared with LPV/r-treated patients may have contributed to the between-group differences in change in BMD at 96 weeks.…”
Section: Discussionmentioning
confidence: 98%